1991
DOI: 10.2466/pr0.1991.68.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Differences in Tactics of Influence

Abstract: Sex and gender differences for 16 tactics of influence were investigated among 292 men and 231 women in higher-level positions. Sex differences indicated that men are more likely to manipulate situations and people, joke or kid, promise rewards, threaten punishments, and use logic or reason. Gender differences indicated that men are perceived as more likely to manipulate situations, be assertive, joke or kid, and threaten punishments, while women are more likely to use charm, appearance, ingratiation, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…Although most researchers have noted that men and women use different infl uence tactics (Carli, 1999;Carothers & Allen, 1999;DuBrin, 1991;Lamude, 1993;White, 1988), many also reported that differences in circumstances correspond to the expectations of normative infl uence behaviors for men and women (Carli, 1999;Carothers & Allen, 1999;Lamude, 1993). For example, Eagly et al (1992) found women to be less effective than men when leading directly.…”
Section: Gendermentioning
confidence: 99%
“…Although most researchers have noted that men and women use different infl uence tactics (Carli, 1999;Carothers & Allen, 1999;DuBrin, 1991;Lamude, 1993;White, 1988), many also reported that differences in circumstances correspond to the expectations of normative infl uence behaviors for men and women (Carli, 1999;Carothers & Allen, 1999;Lamude, 1993). For example, Eagly et al (1992) found women to be less effective than men when leading directly.…”
Section: Gendermentioning
confidence: 99%
“…Tbe employees were designated A tbrougb E to eliminate any effect actual names migbt bave on responses. Researcb indicates tbat men and women differ in tbeir use of and reaction to upward influence tactics (e.g., DuBrin, 1991;Kipnis & Scbmidt, 1988). Altbougb tbe employees' gender was never identified, only male pronouns appeared in tbe logs.…”
Section: Experimental Designmentioning
confidence: 99%
“…Researchers using self-reports have found men are more likely to use a wider range of social desirability techniques (e.g., DuBrin, 1991;Karsten, 1994). Males tend to use more self-enhancement (DuBrin, 1994;Lee, Quigley, Nesler, Corbett, & Tedeschi, 1999;Strutton, Pelton, & Lumpkin, 1994;Tannen, 1994), which is the tendency to maintain a positive self-regard under all circumstances (Dunning, 1999).…”
Section: Previous Research On Sex Differencesmentioning
confidence: 99%
“…This finding coincides with Paulhus's (1984) finding that men engage in more self-deception than women. Researchers have found also that men engage in more favor-doing or exchange than women (e.g., DuBrin, 1991;Higgins & Snyder, 1989;Strutton et al, 1995), acting with entitlement (Lee et al, 1999), using association with others to gain favor (Lee et al, 1999), sandbagging or faking inability (Gibson & Sachau, 2000), self-handicapping (Dietrich, 1995;Hirt, McCrea, & Kimble, 2000;Shepperd & Arkin, 1989), blasting or derogating their competitors (DuBrin, 1991), and intimidation (DuBrin, 1991;Lee et al, 1999;Offermann & Schrier, 1985;Smith et al, 1990).…”
Section: Previous Research On Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation